Diagnosis of Alzheimer's disease by using biological markers in posterior cortical atrophy - D. A. Grishina; N. A. Khayalieva; V. V. Grinyuk; A. Yu. Tyurina (Неврология, нейропсихиатрия, психосоматика, 2024)
The use of biological markers for Alzheimer's disease (AD) allows diagnosis at the stage of moderate cognitive impairment and atypical course of the disease. We present two clinical cases of patients with posterior cortical atrophy (PCA), characterized by progressive impairment of visual and spatial functions due to atrophy of the parietal and occipital lobes of the brain. A differential diagnosis was made between AD, corticobasal degeneration and other diseases in which PCA syndrome occurs. In the cases observed, the patients showed a significant decrease in the level of beta-amyloid in the cerebrospinal fluid, which allowed the diagnosis of AD to be made. Clinical manifestations, diagnosis and treatment of PCA syndrome are discussed. At present, the diagnosis of AD at the stage of moderate cognitive impairment and mild dementia is of practical importance, as anti-amyloid therapy can prevent the progression of AD.